A well-defined low-valent cobalt catalyst Co(PMe3)4 with dimethylzinc: a simple catalytic approach for the reductive dimerization of benzyl halides. (21st November 2016) - Fallon, Brendan J.; Corcé, Vincent; Amatore, Muriel; Aubert, Corinne; Chemla, Fabrice; Ferreira, Franck; Perez-Luna, Alejandro; Petit, Marc
Abstract : We report a simple catalytic version of a cobalt-catalysed reductive homocoupling of benzyl halides by combining Co(PMe3 )4 and Me2 Zn. Abstract : Herein, we report the first catalytic version of a cobalt-catalysed reductive homocoupling of benzyl halides which proceeds with low catalyst loadings (0.5 to 5 mol%). By synthetizing each cobalt intermediate we demonstrate that reaction proceeds through two single electron transfers (SET) and that dimethylzinc is only involved in the regeneration of the catalytic species.